Development of a low-cost team performance tracking system - Aydin, A.; Özgünen, K. T.; Keskinoglu, C.; Talib, E. N.; Dag, N. Y.; Gezgin, E. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Sports technologies are increasingly attracting attention and gaining market share. Since athletes` performance directly affects a team`s success and financial income, tracking their performance is essential.